2021
DOI: 10.1097/bot.0000000000001907
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Uninsured Ankle Fracture: Significant Delays in Treatment Result in an Increased Risk of Surgical Site Infection

Abstract: Objective: To examine the impact of insurance status on access to orthopaedic care and incidence of surgical site complications in patients with closed unstable ankle fractures. Design: Retrospective chart review. Setting: Certified Level-1 urban trauma center and county facility. Participants: Four hundred eighty-nine patients with closed unstable ankle fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Our data suggested that delayed ORIF for closed pilon fracture was associated with an increased risk of SSI, which was consistent with previous reports [ 19 ]. A better understanding of psychosocial and socioeconomic factors was critical to identifying opportunities for further intervention to reduce patient morbidity and healthcare costs [ 12 ]. In addition to increasing the financial burden by prolonging hospital stays or treatment periods, there was also the concern that delaying surgery may increase the risk of complications such as infection or ankle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that delayed ORIF for closed pilon fracture was associated with an increased risk of SSI, which was consistent with previous reports [ 19 ]. A better understanding of psychosocial and socioeconomic factors was critical to identifying opportunities for further intervention to reduce patient morbidity and healthcare costs [ 12 ]. In addition to increasing the financial burden by prolonging hospital stays or treatment periods, there was also the concern that delaying surgery may increase the risk of complications such as infection or ankle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Given the various fracture types analyzed, there is no standard surgical delay known to cause complications so the authors used data from ambulatory ankle fracture literature to guide the analysis. 5 They initially hypothesized that the pandemic would delay care for several weeks beyond the usual time from injury to surgery. If 14 days of additional delay to care were considered to be clinically significant, then a sample size of 12 operative patients would be needed to power the study adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Delays in treatment can result in changes to management, malunion, and increased complications. [5][6][7][8][9] The goals of this study were to characterize the volume of ambulatory orthopaedic fractures that presented to a clinic and the emergency room immediately after the initial implementation of social distancing practices. The authors hypothesized that there would be an overall increased delay in care for ambulatory orthopaedic fracture patients during the early COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limited access to health care for Medicaid patients often delays timely care, even for acute injuries 7,8 . This associated delay in care often leads to worse clinical outcomes 9 .…”
Section: Identifying Underserved Populations: the Uninsured And Under...mentioning
confidence: 99%